The adoption of sustainable construction principles in the design phase in Vietnam - Tran Ngoc Tuyen; Hadikusumo, Bonaventura H. W.; Chotchai Charoenngam; Perera, L.A.S. Ranjith; Cantho Scholarship Program, Vietnam (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Nowadays, the world is more and more concerned with the sustainable development issues. Along with the development, building construction has an important impact on the natural environment. Planning and design stage plays an important decision to the sustainability of one building. The world nowadays has tried to implement many solutions on building design to improve the sustainability. This task depends much on the role of architect and engineer. Being a developing country, Vietnam is trying to implement sustainable development. This study has tried to explore how people are adopting the sustainable building principles in the planning and design stage in Vietnam. The research starts with investigating the perception of the respondents on sustainable construction and sustainable development. And then find out what are the barriers to adopt sustainable construction in Vietnam, along with the incentives to improve the professional toward sustainable construction. In deeply, the study also checks the principles about sustainability in the things starting from the way the architects do the design, the choice of material such as how to choose material that use less energy, material that are less harmful for the environment, material that come from renewable sources, and how the principles be applied at the design stage. The study has found a good perception of the respondents in SD and SC concept. However, the motivation and willingness to implement the SC principles were low due to some reasons and barriers. Beside that, a general overview of what architects are doing design in terms of sustainability principles of the building construction was investigated. Along with the applied principles in the design stage was many useful experiences and lessons from the practical cases in Vietnam. Moreover, a sustainable development and construction framework during design stage was proposed, and also some suggestion principles were given for the architect to apply in the design stage in Vietnam
Submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Construction Engineering and Infrastructure Management
Thesis (M.Eng.) - Asian Institute of Technology, 2008
Keywords: Construction industry -- Vietnam